'Is Help Coming?' Communal Self-Protection during Genocide. Issue 1 (14th May 2020) - Mayersen, Deborah
Despite the rhetoric of the Responsibility to Protect principle (R2P), vulnerable groups continue to experience genocide. Some, such as the Yazidis in Iraq, have tried to mitigate genocide through communal self-protection. The dominance of R2P in contemporary normative discussions about responding to genocide, however, means that there has been a lack of research into the lived realities of such experiences. This article explores the phenomenon of communal self-protection during genocide, through a multiple case study analysis. It examines the pre-eminent examples of communal self-protection during three cases of modern genocide — the experiences of the Armenians at Musa Dagh during the 1915 Armenian genocide, the Tutsi at Bisesero during the 1994 Rwanda genocide, and the Yazidis in Sinjar during the 2014 Yazidi genocide. It presents a typology of communal self-protection strategies during genocide, developed from the case study analysis. The article finds that communal self-protection is only feasible as a strategy in exceptional circumstances. Even in a best-case scenario, communal self-protection offers a temporary reprieve, rather than sustainable living conditions. Vulnerable groups attempting communal self-protection are ultimately reliant on external rescue for their survival, which may not be forthcoming. Communal self-protection should therefore not be regarded as a viable strategy to mitigate genocide in any circumstance.